NONEXISTENCE AND ABOUTNESS: THE BANDERSNATCHES OF DUBUQUE - Yablo, Stephen (Crítica; revista hispanoamericana de filosofía, 2020)
Holmes exists is false. How can this be, when there is no one for the sentence to misdescribe? Part of the answer is that a sentence’s topic depends on context. The king of France is bald, normally unevaluable, is false qua description of the bald people. Likewise Holmes exists is false qua description of the things that exist; it misdescribes those things as having Holmes among them. This does not explain, though, how Holmes does not exist differs in cognitive content from, say, Vulcan does not exist. Our answer builds on an observation of Kripke’s: even if Holmes exists, he is not in this room, for we were all born too late. Holmes existe es falsa. ¿Cómo puede ser, cuando no hay nadie acerca de quien puede ser la oración? Parte de la respuesta es que el tema de la oración depende del contexto. Así como El rey de Francia es calvo, normalmente imposible de ser evaluada, es falsa qua descripción de la gente calva, Holmes existe es falsa qua descripción de las cosas que existen; describe mal esas cosas como si Holmes estuviera entre ellas. Esto no explica, sin embargo, cómo Holmes no existe difiere en valor cognitivo de, digamos, Vulcano no existe. Nuestra respuesta se construye a partir de una observación de Kripke: aun cuando Holmes exista, no está en este cuarto, porque todos nacimos demasiado tarde.